A novel role for integrin‐linked kinase in periodic mechanical stress‐mediated ERK1/2 mitogenic signaling in rat chondrocytes. (17th May 2016) - Song, Huanghe; Liang, Wenwei; Xu, Shun; Li, Zeng; Chen, Zhefeng; Cui, Weiding; Zhou, Jinchun; Wang, Qing; Liu, Feng; Fan, Weimin
Abstract: In recent years, a variety of studies have been performed to investigate the cellular responses of periodic mechanical stress on chondrocytes. Integrin β1‐mediated ERK1/2 activation was proven to be indispensable in periodic mechanical stress‐induced chondrocyte proliferation and matrix synthesis. However, other signal proteins responsible for the mitogenesis of chondrocytes under periodic mechanical stress remain incompletely understood. In the current investigation, we probed the roles of integrin‐linked kinase (ILK) signaling in periodic mechanical stress‐induced chondrocyte proliferation and matrix synthesis. We found that upon periodic mechanical stress induction, ILK activity increased significantly. Depletion of ILK with targeted shRNA strongly inhibited periodic mechanical stress‐induced chondrocyte proliferation and matrix synthesis. In addition, pretreatment with a blocking antibody against integrin β1 resulted in a remarkable decrease in ILK activity in cells exposed to periodic mechanical stress. Furthermore, inhibition of ILK with its target shRNA significantly suppressed ERK1/2 activation in relation to periodic mechanical stress. Based on the above results, we identified ILK as a crucial regulator involved in the integrin β1‐ERK1/2 signal cascade responsible for periodic mechanical stress‐induced chondrocyte proliferation and matrix synthesis.